2020
DOI: 10.1039/d0dt01204a
|View full text |Cite
|
Sign up to set email alerts
|

An iron variant of the Noyori hydrogenation catalyst for the asymmetric transfer hydrogenation of ketones

Abstract: A new type of iron catalyst that structurally mimics the Noyori hydrogenation catalyst can catalyze the asymmetric transfer hydrogenation of ketones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 127 publications
0
5
0
Order By: Relevance
“…Although Meerwein–Ponndorf–Verley reduction has been widely utilized in both academic and industrial processes, the major drawbacks of this protocol are the requirement of a large amount of aluminum alkoxide reagent, unwanted side reactions, and moisture sensitivity of aluminum alkoxides. Over the last few decades, transfer hydrogenation of multiple bonds between carbon and heteroatoms (such as oxygen and nitrogen in carbonyls and imines, respectively) is a very active field of research and a large variety of homogeneous transition metal catalysts based on iron, ruthenium, osmium, cobalt, rhodium, iridium, nickel, palladium, and gold , have been developed. However, most of the efficient transfer hydrogenation protocols utilized ruthenium-, rhodium-, or iridium-based catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…Although Meerwein–Ponndorf–Verley reduction has been widely utilized in both academic and industrial processes, the major drawbacks of this protocol are the requirement of a large amount of aluminum alkoxide reagent, unwanted side reactions, and moisture sensitivity of aluminum alkoxides. Over the last few decades, transfer hydrogenation of multiple bonds between carbon and heteroatoms (such as oxygen and nitrogen in carbonyls and imines, respectively) is a very active field of research and a large variety of homogeneous transition metal catalysts based on iron, ruthenium, osmium, cobalt, rhodium, iridium, nickel, palladium, and gold , have been developed. However, most of the efficient transfer hydrogenation protocols utilized ruthenium-, rhodium-, or iridium-based catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…The use of EtOH as hydrogen source complements the more commonly employed isopropanol and formic acid and offers major benefits, as it is widely available, environmentally friendly, and a very low-cost hydrogen source. The major reason for the scarce utilization of primary alcohols as hydrogen sources is their unfavorable redox potential.…”
Section: Resultsmentioning
confidence: 99%
“…Following Chen’s synthetic strategy, , we introduce P-chirogenic substituents diastereoselectively into the ferrocene backbone. Following the previous strategy of our group, we introduce the aldehyde group without racemization and cleavage of the P-chirogenic phosphino group.…”
Section: Resultsmentioning
confidence: 99%
“…of 95%. To explain the reasons why catalyst 2n generated the ( S )-configuration products with relatively high enantioselectivities, we analyzed the interaction energies of the substrate and intermediate 3n in the transition state with Multiwfn software, using the EDA-FF method based on the molecular force field (Figure b). ,, The analytical results showed that the ( S )-configuration of the phosphine kept the ( S )-planar chiral ferrocene group far from the reacting site in the TS S ‑ACP transition state. This provided enough space for the aryl ring of the substrate and the ene­(amido) moiety of the catalyst to approach each other, resulting in the formation of a strong π–π interaction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation